การศึกษากลุ่มอาการ การจัดการ และผลลัพธ์ของการจัดการของผู้ป่วยที่มีภาวะกล้ามเนื้อหัวใจตายเฉียบพลัน - ปฏิญญา สงวนพงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purpose of this descriptive research was to study symptom clusters, symptom management and outcome of management of patients with acute myocardial infarction. The sample consisted of 80 patients admitted to Hatyai Hospital, Trang Hospital, Maharat Nakronsrithamarat Hospital and suratthanee Hospital. The instrument consisted of 3 parts: a demographic data from, a symptom cluster questionnaire, and an interview guide for symptom cluster management and outcome. The test-retest reliability of the symptom cluster questionnaire revealed a percentage agreement of 0.81. Cronbach’s Alpha Coefficient of the symptom cluster management of 0.73. Data were analyzed using descriptive statictics and content analysis. The results revealed that: 1. The most prominent symptom was chest pain (91.3%) and chest pain was also reported as the primary originating symptom (91.25%). 2. The symptom cluster management strategies reported by the subjects were stop activity (X-bar = 2.99, SD=0.54) and take vasodilatation medicine (X-bar = 1.16 , SD=1.5). 3. The outcomes of symptom cluster management reported by most patients was getting worse (56.25%), no change (18.75%), and getting better (25%).